2019
DOI: 10.1016/j.electacta.2019.03.080
|View full text |Cite
|
Sign up to set email alerts
|

On the corrosion mechanism of Mg investigated by electrochemical impedance spectroscopy

Abstract: This work reported a detailed analysis of the electrochemical impedance spectra obtained for the Mg electrode during immersion in a sodium sulfate solution. A model was proposed which took into account the presence of: (i) a thin oxide film (MgO) which progressively covered the Mg electrode surface, (ii) film-free areas where the Mg dissolution occurs in two consecutive steps, (iii) a thick layer of corrosion products (Mg(OH) 2), (iv) an adsorbed intermediate ðMg þ ads Þ which is responsible for the chemical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
89
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 208 publications
(96 citation statements)
references
References 63 publications
(63 reference statements)
6
89
1
Order By: Relevance
“…The quality of the fit is attributed to the fact that there were slow changes in the corrosion rate in the present work as is evident from Figures . The fit was not as good as those by Gomes et al and those of Scully and co‐workers; however, those works used solutions that were much less corrosive, so the corrosion behavior was much more stable, and there was much less change in corrosion behavior during the measurement of EIS spectra. The corrosion rates evaluated from the EIS data, P i,EIS,1 and P i,EIS,2 , were consistently smaller than the corrosion rates evaluated from the evolved hydrogen P H .…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…The quality of the fit is attributed to the fact that there were slow changes in the corrosion rate in the present work as is evident from Figures . The fit was not as good as those by Gomes et al and those of Scully and co‐workers; however, those works used solutions that were much less corrosive, so the corrosion behavior was much more stable, and there was much less change in corrosion behavior during the measurement of EIS spectra. The corrosion rates evaluated from the EIS data, P i,EIS,1 and P i,EIS,2 , were consistently smaller than the corrosion rates evaluated from the evolved hydrogen P H .…”
Section: Resultsmentioning
confidence: 62%
“…Gomes et al found that steady‐state corrosion for pure Mg in 0.1 M Na 2 SO 4 , for times between 2 and 58 hr, was consistent with a reaction sequence involving the Mg + ion as an intermediate, occurring mainly in the breaks in the MgO surface film, 5–7 nm thick. These breaks in the MgO layer represented a fraction of ≈0.003 of the surface.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…It should be noted that it is this last contribution that is analyzed when using the complex capacitance representation to determine the thickness of the oxide films formed on the surface of the electrodes. [17][18]33 The parameter determined from the fitting procedure is 0.77, and will be further discussed in the following section.…”
Section: Aluminum Electrodementioning
confidence: 99%